Efektivitas Program Hortimart Kepri dalam Pemasaran Cabai di Kota Batam (Jurnal Agribisnis dan Agrowisata, 2025)
Effectivity of the Hortimart Kepri Program in Chili Marketing in Batam City. Farmer’s dependence on middlemen prompted the Batam City Agriculture and Food Security Service to create a program called Hortimart Kepri which aims to be a partner for farmers so that they have their own marketing channels to secure prices both at the farmer level and at the consumer level. This research aims to determine the effectiveness of the Hortimart Kepri Program by using a marketing analysis approach to determine patterns, efficiency (marketing margin, farmer's share, profit and cost ratio), as well as marketing institutions and functions. The respondents in this research were 60 people including farmers, Hortimart Kepri, middlemen, wholesalers and retailers. The results showed that there are two marketing channel patterns, namely: (1) Farmers - Hortimart Kepri, (2) Farmers - Middlemen - Wholesalers - Retailers. The marketing margin for marketing channel pattern I is IDR. 4,200,-/kg, farmer's share percentage of 85%, and profit to cost ratio of 2.32. Marketing channel pattern II on the other hand has a marketing margin of Rp. 12,700/kg, the farmer's share percentage is 69.59%, and the profit to cost ratio is 1.60. Each institution in each marketing channel pattern carries out three marketing functions, namely the exchange function, physical function and facility function.
Keywords: effectivity; hortimart kepri; marketing; chili